Is It Really Happening? The Postmodern Horror of Roman Polanski’s Rosemary’s Baby - Carstensen, Thorsten (American Studies in Scandinavia, 2023)
This article examines Roman Polanski’s film Rosemary’s Baby (1968) as both a symptom and a manifestation of the cultural and political upheavals of the late 1960s. Released in an era marked by rampant conspiracy theories and a growing opposition to established hierarchies and institutions, the film constitutes a prime example of “paranoid horror.” Reflecting the collapse of commonly accepted metanarratives such as religion and the American nuclear family, Rosemary’s Baby adamantly rejects the restoration of order that earlier horror movies would have provided. In fact, by questioning ontological reliability, it epitomizes the shift from the classical to the postmodern horror narrative.